Sharply rising prevalence of HIV infection in Bali: a critical assessment of the surveillance data. (August 2013) - Januraga, P P; Wulandari, L P L; Muliawan, P; Sawitri, S; Causer, L; Wirawan, D N; Kaldor, J M
Summary: This study critically examines serological survey data for HIV infection in selected populations in Bali, Indonesia. Sero-survey data reported by the Bali Health Office between 2000 and 2010 were collated, and provincial health staff were interviewed to gain a detailed understanding of survey methods. Analysis of time series restricted to districts that have used the same sampling methods and sites each year indicates that there has been a steady decline in HIV prevalence among prisoners, from 18.7% in 2000 to 4.3% in 2010. In contrast, HIV prevalence among women engaged in sex work increased sharply: from 0.62% in 2000 to 20.2% in 2010 (brothel based), and from 0% in 2000 to 7.2% in 2010 (non-brothel based). The highest prevalence was recorded among people who injected drugs. Recent surveys of gay men and transvestites also found high prevalences, at 18.7% and 40.9%, respectively. Review of the methodology used in the surveys identified inconsistencies in the sampling technique, sample numbers and sites over time, and incomplete recording of individual information about survey participants. Attention to methodological aspects and incorporation of additional information on behavioural factors will ensure that the surveillance system is in the best position to support prevention activities.